2003
DOI: 10.1046/j.1365-2923.2003.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reasoning strategies and diagnostic success

Abstract: These findings have significant implications for medical educators. It supports the introduction of "schemes" as a means of enhancing memory organization and improving diagnostic success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
267
0
22

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(294 citation statements)
references
References 23 publications
5
267
0
22
Order By: Relevance
“…Novices on the other hand have been found to use analytic reasoning strategies in favour of non-analytic strategies because they do not have enough experiential knowledge (Bowen 2006). Conversely, recent studies showed that pattern recognition is a powerful tool in diagnostic accuracy in experts as well as in novices after they had been explicitly instructed to use pattern recognition, especially when used in combination with other reasoning strategies (Coderre et al 2003;Ark et al 2007). The results of our study suggest that medical students, who are clearly novices, are able to develop and use both ways of clinical reasoning even without explicit instruction but with real patients as the driving force for their learning.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Novices on the other hand have been found to use analytic reasoning strategies in favour of non-analytic strategies because they do not have enough experiential knowledge (Bowen 2006). Conversely, recent studies showed that pattern recognition is a powerful tool in diagnostic accuracy in experts as well as in novices after they had been explicitly instructed to use pattern recognition, especially when used in combination with other reasoning strategies (Coderre et al 2003;Ark et al 2007). The results of our study suggest that medical students, who are clearly novices, are able to develop and use both ways of clinical reasoning even without explicit instruction but with real patients as the driving force for their learning.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…On peut cependant penser, même si cela reste à démon-trer, qu'une mémorisation « syndromique » des données conduira préférentiellement à l'utilisation des stratégies de résolution de type syndromique, tout comme une mémorisation d'organigrammes déci-sionnels sera de nature à favoriser la résolution de problème en utilisant des signes discriminants. [12] Penser à voix haute 4 problèmes cliniques de 41 % 59 % + gastro-entérologie non complexes analyse instantanée (un seul diagnostic possible) Internes en 1 e année de 3 e cycle Penser à voix haute Résoudre 11 problèmes 64 % 36 % de médecine générale [11] + cliniques complexes Internes en 1 e et 2 e année analyse différée Idem 62 % 38 % de DES de médecine [11] sur les verbatims Internes en DES enregistrés QROC ou QCM longue liste 46 % 54 % de médecine interne [4] Spécialistes en médecine Penser à voix haute 4 problèmes cliniques complexes 40 % 60 % interne (1 à 15 ans + simulés par écrit d'expérience) cartes conceptuelles Spécialistes en néphrologie [11] Penser à voix haute Résoudre 11 problèmes 63 % 37 % + cliniques complexes analyse différée sur les verbatims enregistrés Spécialistes en gastro-entérologie Penser à voix haute 4 problèmes cliniques de 94 % 6 % (plus de 5 ans d'expérience) [12] + gastro-entérologie non complexes analyse instantanée (un seul diagnostic possible) TRI : Taux de raisonnement inductif. TRD : Taux de raisonnement déductif.…”
Section: Discussionunclassified
“…En revanche, Coderré et al [12,13] montrent une prépondérance du raisonnement inductif chez les experts (jusqu'à 96 %). Dans le cadre de leurs travaux, la résolution du problème était rendue explicite par des réponses à deux types de questions à choix multiples (QCM) comprenant soit moins de 5 options, soit plus de 10 options.…”
Section: Discussionunclassified
See 2 more Smart Citations